(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Describe the compliance of private specialized clinics with a number of legal regulations. Subject and method: Using a cross- sectional description, research subjects are all of the private specialized clinics in Son La city, total sample size of 75 clinics and manager. Result: There are 77.3% of facilities that fully comply with the regulations of the law on private medical examination and treatment, 22.7% comply but not fully. Criteria for general conditions of facilities have an achievement rate of 85.3%; The criteria for ensuring medical equipment is 96%, the standard for responsible professionals and practitioners is 94.7%. Conclusion: Department of Health and Medical Center Further strengthen management measures, paying special attention to inspection, examination and sanctioning of administrative violations of private medical examination and treatment and have effective handling measures.